Marília de Dirceu: Mimese e alteridade em diálogo na poesia lírica brasileira do século XVIII - Simões, Luís Carlos (2007)
This monograph deals with the limits between the literary entity named lyrical self , created by an author, and the real world entity that created the text who is the poet himself. For such a task we chose as an object for this research one of the most popular texts from Brazilian Poetry: Marília de Dirceu written by Tomas Antonio Gonzaga in the late XVIII century. The choice of this work was motivated not only for its popularity among poetry readers, but especially because we believe that in this text the limits or boundaries between the lyrical self and the poet are so fragile that even the autobiographical features of the author are now projected on to the lyrical self in a kind of narcissistic mirror. However, one of the most essential characteristics of Arcadian Poetry (Arcadismo) is the pastoral convention where the poet pretends to be a "shepherd" that gives voice to this fictional entity instead of his true self and his personal biography. That is one of the reason why Gonzaga's text represents a breakthrough from the traditional thinking of Arcadian Poetry. From a methodology of theoretical investigation into the concepts of language, discourse and literature, we try to understand the construction of the poem, its lyricism and how through the literary mimesis the alterities of the poetical text are established. All these are fundamental to the understanding of Arcadian Poetry. With these theoretical considerations and a brief research into the origins of Arcadian Poetry and its manifestations in Portugal and Brazil we tried to verify our hypothesis in the lyric poems created by Gonzaga. The result made us realize that the Arcadian canons were in fact followed in part of the work especially when the lyrical self as the character called Dirceu idealizes a happy world with his beloved Marília. Nevertheless, when Gonzaga is arrested suspected of taking part in Inconfidência Mineira and he has to write in prison, both the poet and the "shepherd" are now intermingled with each other reflecting the mutual dependency that both have and thus making the boundaries between fiction and reality even more delicate